Expression of TIP60 (tat‐interactive protein) and MRE11 (meiotic recombination 11 homolog) predict treatment‐specific outcome of localised invasive bladder cancer - Laurberg, Jens R.; Brems‐Eskildsen, Anne S.; Nordentoft, Iver; Fristrup, Niels; Schepeler, Troels; Ulhøi, Benedicte P.; Agerbæk, Mads; Hartmann, Arndt; Bertz, Simone; Wittlinger, Michael; Fietkau, Rainer; Rödel, Claus; et al. (BJU international, 2012)
What's known on the subject? and What does the study add? Several studies have shown that defects in DNA‐damage response are associated with good survival after chemotherapy and radiotherapy. Furthermore, loss of cell cycle regulators may be prognostic indicators of poor survival after cystectomy. However, the potential clinical impact of previous findings is hampered by insufficient validation of significant results in suitable cystectomy and radiotherapy cohorts. Here we use a large cohort of patients receiving radiotherapy to successfully validate the importance of MRE11 as a predictive marker of disease‐specific survival (DSS). Furthermore, using two independent patient cohorts we show for the first time that TIP60 is a predictive marker of DSS after cystectomy. We show that combined use of TIP60 and MRE11 may hold the potential to guide treatment decisions. OBJECTIVE • To determine the association between the proteins: tat‐interactive protein 60 kDa (TIP60), p16, meiotic recombination 11 homolog (MRE11), phosphorylated ataxia telangiectasia mutated (ATM), retinoblastoma protein (Rb), Ki67, and p53 and clinical outcome in invasive lymph node‐negative bladder cancer. PATIENTS AND METHODS • Protein expression was measured by immunohistochemistry in cancer specimens from two independent cohorts of patients with bladder cancer treated with cystectomy (162 patients and 273) and one cohort of patients receiving radiotherapy (148). • Disease‐specific survival (DSS) was used as the outcome measure, and patients with no disease‐specific death were followed for a minimum of 36 months. RESULTS • TIP60 was significantly correlated with DSS in both cystectomy cohorts (hazard ratio [HR] 0.42, 95% confidence interval [CI] 0.26–0.68, P < 0.001 and HR 0.45, 95% CI 0.28–0.72, P= 0.001). • MRE11 was significantly correlated with DSS in the cohort receiving radiotherapy (HR 0.64, 95% CI 0.47–0.86, P= 0.005). • P16 was significantly correlated with DSS in all three cohorts (HR 0.46, 95% CI 0.30–0.75, P= 0.032; HR 0.60, 95% CI 0.37–0.97, P= 0.032; HR 0.52, 95% CI 0.28–0.96, P= 0.001). • Rb was significantly correlated with DSS in one cystectomy cohort (HR 1.71, 95% CI 1.13–2.75, P= 0.017). • Ki67, p53, and pATM were not significantly correlated with DSS in any of the cohorts. CONCLUSIONS • TIP60 protein expression was a predictive marker for DSS after cystectomy in two independent cohorts. This novel marker was the strongest predictive factor in multivariate analysis in patients receiving cystectomy. • MRE11 was shown to be a predictive marker for DSS after radiotherapy. • We have shown that TIP60 and MRE11 hold the potential to guide patients with invasive bladder cancer to either cystectomy or radiotherapy. This study was based on retrospective material and consequently we suggest that these markers should be validated in a prospective study.